Optogenetic dissection of ictal propagation in the hippocampal–entorhinal cortex structures - Yi Lu (Nature Portfolio, 2016)
The network mechanism supporting seizure spread in temporal lobe epilepsy (TLE) is only partially understood. Using optogenetic methods, Lu et al.identify a feed-forward propagation pathway of ictal discharges from the dentate gyrus/hilus to the medial entorhinal cortex in a mouse model of TLE.